2022
DOI: 10.2807/1560-7917.es.2022.27.33.2200603
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox self-diagnosis abilities, determinants of vaccination and self-isolation intention after diagnosis among MSM, the Netherlands, July 2022

Abstract: Monkeypox is a zoonotic disease and leads to a smallpox-like disease in humans. The current epidemic in European countries requires informed responses. We investigated the ability to self-diagnose a potential infection, and determinants of vaccination and self-isolation intention after diagnosis among 394 MSM in the Netherlands. We found that about half were able to self-diagnose monkeypox, that 70% had a high intention to get vaccinated and 44% to self-isolate after monkeypox diagnosis. Determinants went beyo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 8 publications
6
45
1
Order By: Relevance
“…Acceptance of the Monkeypox vaccination in HCWs is limited in the case of a specific recommendation for professional exposure, but is not very far from the acceptance rate observed in men having sex with men (MSM) in the Netherlands if the vaccine become recommended in the general population [7]. Different hypotheses can be made.…”
Section: Factors Associated With Intention To Get Vaccinated Against ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Acceptance of the Monkeypox vaccination in HCWs is limited in the case of a specific recommendation for professional exposure, but is not very far from the acceptance rate observed in men having sex with men (MSM) in the Netherlands if the vaccine become recommended in the general population [7]. Different hypotheses can be made.…”
Section: Factors Associated With Intention To Get Vaccinated Against ...mentioning
confidence: 99%
“…Complacency for Monkeypox is probably a great barrier for vaccine acceptance. In MSM, in the Netherlands, perceived risk of being infected and risky sexual behaviors did not predict attitudes toward vaccination, while having concern about being infected was associated with intention to get vaccinated [7]. Then, in the context of the epidemics, the large use of personal protective equipment may also give to HCWs a sense of security.…”
Section: Factors Associated With Intention To Get Vaccinated Against ...mentioning
confidence: 99%
“…The survey identified differences in intention among respondents based on social determinants such as education and migration status. (14) Research on previous MPXV outbreaks has shown that working with affected communities and leveraging digital media can support community uptake. (15-17) Although evidence on MPXV is only starting to emerge, structural barriers will remain a key issue in all outbreak responses.…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed 263 subjects: 260 (98.9%) were men; median age was 38 years-old (interquartile range, (IQR) [30-50]) and 115/263 (43.7%) were born before 1980 ( Table 1 ). Two-hundred fifty-five participants (255/260, 98.1%) identified as MSM, and median number of sexual partners within the 30 days prior to vaccination was of 3 ([ 2 , 3 , 4 , 5 , 6 ]). Two-hundred and sixteen (216/263, 82.1%) subjects had at least a Bachelor’s degree.…”
mentioning
confidence: 99%
“…Indeed, Mailhe and colleagues reported a cohort study of 264 patients with proven Monkeypox infections in France in which 262 patients (262/264, 99%) were men, 245 (245/259, 95%) were MSM and seventy-three (73/256, 29%) were PLVIH [ 1 ]. Our population, with 39.1% HIV PrEP user, and 82.1% with higher education, corresponds to a population with high intention to get vaccinated [ 3 ]. We identify a “high confidence, low literacy” vaccinee profile, confirming the importance of confidence in vaccine uptake [ 4 ].…”
mentioning
confidence: 99%